Francesco da Barberino al crocevia : Culture, società, bilinguismo - Montefusco, Antonio; Bischetti, Sara; Montefusco, Antonio; Bischetti, Sara (Berlin/Boston De Gruyter, 2021)
This volume presents an interesting case study dealing with the relationship between bilingualism and society in 14th-century Florence. Francesco da Barberino s Documenta Amoris are a sort of orthodox contrappunto of the Commedia, in which Dante s linguistic experimentation is substituted by Francesco s rigid bilingualism. The book provides one of the first interpretations of this fundamental figure of 14th-century Florentine culture.
H2020 European Research Council
Italian
Keywords: Sociolinguistics; Bilingualism & multilingualism; Historical & comparative linguistics; Literary studies: classical, early & medieval; Early modern history: c 1450/1500 to c 1700; Francesco da Barberino; Medieval Bilingualism; Medieval Italy; Italian Medieval Studies